Lindungi Imunitas Masyarakat Dengan Minuman Herbal - Uswatun Hasanah, Siti; Diki Prayugo Wibowo; Diah Lia Aulifa (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The aim of PKM is to increase public knowledge in an effort to increase the body’s resistance of community members during the Covid 19 pandemic. The method of activity is to form a team of extension agents (women for Family Welfare Empowerment), accompanied by providing samples of herbal drink products and companion brochures. The results achieved from this activity, the community can get to know several medicinal plants that have immune-enhancing properties, along with a simple processing process.